The Role of Job Stress as A Mediator Between Toxic Workplace Environment and Organizational Support on Employee Well Being - Umroti, Sofa Niskiyatul; Suhana, Suhana (JURNAL STUDI MANAJEMEN ORGANISASI, 2025)
This research alms to explore the role of job stress as a mediator in the relationship between a toxic workplace environment and organizational support in relation to employee well being among civil servants at the Regional Secretariat of Pekalongan City. The study adopts a quantitative approach with an explanatory design. Data were collected through questionnalres distributed to 101 respondents and analyzed using regression analysis and the Sobel test. The results indicated that a toxic workplace environment has a positive impact on job stress, while organizational support has a negative impact on job stress. However, the toxic workplace environment doesn't affect employee well being, whereas organizational support positively influences employee well being. These findings suggest that organizational support has a more dominant role in improving employee well being compared to the influence of job stress or toxic workplace environment. Therefore, government institutions are advised to prioritize strengthening organizational support as a strategic step in an effort to improve employee well being.